Pelatihan Pembuatan Handsoap Otomatis - Tholib Hariono; Hilyah Ashoumi; Muchamad Wahyu Chabibullah (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
The purpose of implementing this service is to increase public awareness of the importance of washing hands and obeying health protocols. The approach method for implementing community service activities in the KKN-PPM scheme includes lectures, discussions, and workshops (training) methods. Based on the results of community service activities in the KKN-PPM scheme, it can be concluded as follows; 1) Provide additional insight and knowledge and skills to the youth of Banjarsari village to be able to create and implement it in community life. 2) Growing new passion for the youth of Banjarsari village in carrying out learning activities where there is an increase in skills related to assembling automatic hand sanitizers and making natural ingredients.